THE IMPACT OF INSTAGRAM AS A SOCIAL MEDIA TOOL ON CONSUMER PURCHASE DECISION ON NIKE - Ni Putu Eni Diantari; Jean Richard Jokhu (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
The world has been changed and globalized with technology's revolution with communication and the spread of information, while social media is now known as an important part of marketing strategies. Instagram is one of the social media platforms that most people use. Nike is one of the market leaders sneakers brand in the world but in Indonesia, there is a decreasing band index of Nike in the last three years. Therefore, the researcher conducted a study to analyze the factor that could influence customer purchase decisions and focused on Nike brands. This study using celebrity endorsement, Instagram advertising, E-WOM, perceived quality as the X variable with brand awareness as a mediating variable. This research used a quantitative method using PLS-SEM to analyze the respondent (n= 305) who in age 20-40 which is the Millennials generation. The result showed that perceived quality did not significantly influence both purchase decision and brand awareness. Whereas celebrity endorsement, Instagram advertising, and E-WOM significantly influence consumer purchase decisions and brand awareness. This research also found that brand awareness has a positive relationship with the purchase decision.